PENGEMBANGAN LEMBAR KERJA SISWA BERBASIS MULTIPLE INTELLIGENCES PADA MATERI PERTUMBUHAN DAN PERKEMBANGAN (Journal of Biology Education, 2013)
This study aimed to develop and assess feasibility of student worksheet on Growth and Development topics, based on multiple intelligences theory, as well as to measure the effectiveness of  the student worksheet. Research design used  was one of research and development modified from Sugiyono (2010), and was based on students’ intelligences identification and teaching materials analyzed. LKS validation results were analyzed with descriptive percentages. Small-scale testing was  carried out on 1 teacher and 12 students to assess worksheets legibility. Large-scale field-testing was carried out on one teacher and 36 students to measure student worksheets’ effectiveness. Results of student worksheet development based on multiple intelligences theory in terms of  its material feasibility aspects was  96,87% (obtained score) and media feasibility 89,56% under medium category. Normalized gain score was 0,65, indicating that  there was an increasing learning achievement  from pretest to posttest under medium category. Classical completeness of  students reached 88,89%. The use of  the student worksheet for  learning process was appreciated ‘ very good responses’ by  teachers and students, 100% and 88,69%. Student worksheet development  on the basis of multiple intelligence theories for  Growth and Development topics was  feasible and effectively applied for  learning. Penelitian bertujuan untuk mengembangkan dan mengetahui kelayakan Lembar Kerja Siswa (LKS) berbasis multiple intelligences pada materi pertumbuhan dan perkembangan serta mengukur keefektifan LKS dalam pembelajaran. Penelitian menggunakan metode penelitian pengembangan (Research and Development) dimodifikasi dari Sugiyono (2010) berdasarkan hasil identifikasi kecerdasan siswa dan analisis kebutuhan bahan ajar. Hasil validasi LKS dianalisis dengan deskriptif persentase. Uji coba skala kecil dilakukan terhadap 1 guru dan 12 siswa untuk menilai keterbacaan LKS. Uji coba skala besar dilakukan terhadap 1 guru dan 36 siswa untuk mengukur efektivitas LKS dalam pembelajaran. Hasil pengembangan LKS berbasis multiple intelligences aspek kelayakan materi memperoleh skor 96,87% dan kelayakan media 89,56% dengan kategori sangat layak. Nilai gain ternormalisasi sebesar 0,65 menunjukkan adanya peningkatan hasil belajar dari pretest ke posttest dengan kategori sedang. Ketuntasan klasikal siswa mencapai 88,89%. Penggunaan lembar kerja siswa dalam pembelajaran memperoleh tanggapan sangat baik dari guru dan siswa dengan persentase 100% dan 88,69%. Pengembangan lembar kerja siswa berbasis multiple intelligences pada materi pertumbuhan dan perkembangan layak dan efektif diterapkan dalam pembelajaran.